EDMODO-BASED BLENDED LEARNING MODEL ON NEWS TEXT MATERIALS FOR CLASS VIII - Fitri, Tifani Nurul; Diana, Purwati Zisca (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study and development are motivated by the use of internet-based technology that has not beenÂ maximized in learning in schools, especially junior high schools. Therefore, the purpose of this study is toÂ develop a learning model that combines the learning proces directly throught face-to-face online learningÂ through applications, so that researchers develop a blended learning model based on edmodo in learningÂ news text for class VIII SMP. This study uses the research and development (R & D) method, with the ADDIEÂ model development procedure, namely the analysis, design, development, implementation, and evaluationÂ steps. The results of this study indicate that the learning model that has been developed can be categorized asÂ "very feasible". This is evidenced by the average score of 82. The average score obtained from materialÂ experts is 87, from media experts is 74, and from teaching experts is 85. Based on this, it can be concludedthat the study and development of this learning model can be a supplement in learning so that students areÂ more active and independent.AbstrakPenelitian dan pengembangan ini dilatarbelakangi oleh adanya penggunaan teknologi berbasis internet yang belum maksimal dalam pembelajaran di sekolah, khususnya sekolah menengah pertama (SMP). Oleh sebab itu, tujuan penelitian ini adalah untuk mengembangkan model pembelajaran yang menggabungkan proses pembelajaran secara langsung melalui tatap muka maupun pembelajaran secara daring melalui aplikasi, sehingga peneliti mengembangkan model pembelajaran blended learning berbasis edmodo pada pembelajaran teks berita kelas VIII SMP. Penelitian ini menggunakan metode research and development (R & D), dengan prosedur pengembangan model ADDIE yakni dengan langkah analysis, design, development, implementation, and evaluation. Hasil penelitian menunjukkan bahwa model pembelajaran yang telah dikembangkan dapat dikategorikan â€œsangat layakâ€. Hal tersebut dibuktikan dengan hasil skor rata-rata sebesar 82. Rata-rata skor yang diperoleh dari ahli materi sebesar 87, dari ahli media sebesar 74, dan dari ahli pengajaran sebesar 85. Berdasarkan hal tersebut dapat disimpulkan bahwa penelitian dan pengembangan model pembelajaran ini, dapat menjadi suplemen dalam pembelajaran agar peserta didik lebih aktif dan mandiri